2020
DOI: 10.1186/s40478-019-0875-3
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Comprehensive gene expression meta-analysis identifies signature genes that distinguish microglia from peripheral monocytes/macrophages in health and glioma

Abstract: The original publication of this article [1] contained 3 minor errors in Figs. 1, 3 and 5. In this correction article the updated figures are published. The figure captions describe the updated information in these figures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 1 publication
2
76
0
Order By: Relevance
“…From 2013–2017 in the United States, the incidence of brain and other nervous system cancers in patients aged 0–19 was 3.2 per 100,000 [ 56 ]. Pediatric gliomas, including pilocytic astrocytoma, are the most common type of pediatric brain tumour [ 90 , 91 ].…”
Section: Gliomamentioning
confidence: 99%
“…From 2013–2017 in the United States, the incidence of brain and other nervous system cancers in patients aged 0–19 was 3.2 per 100,000 [ 56 ]. Pediatric gliomas, including pilocytic astrocytoma, are the most common type of pediatric brain tumour [ 90 , 91 ].…”
Section: Gliomamentioning
confidence: 99%
“…NDUFB5 or nicotinamide adenine dinucleotide dehydrogenase (ubiquinone) 1 beta subcomplex 5, is a nuclear-encoded mitochondrial protein which functions as part of complex 1 of the electron transport chain. Many studies have shown NDUFB5 levels is altered in disease, typically coupled with altered expression of other mitochondrial respiratory proteins [ 63 , 64 , 65 , 66 ]. In the context of AD, NDUFB5 has been suggested as a hub protein associated with disease pathogenesis based on co-expression analyses [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies used, 55% utilized microarray experiments, 40% used RNA sequencing and 5% were based on single cell RNA sequencing experiments. In total, transcriptomic data of 39 studies was acquired [ 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 ].…”
Section: Methodsmentioning
confidence: 99%